2007
DOI: 10.1021/ic700420w
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fluorescence Zinc Ion Sensing and Binding Behavior of 4-Methyl-2,6-bis(((phenylmethyl)imino)methyl)phenol:  Biological Application

Abstract: Zinc ion fluorescence sensing and the binding properties of 4-methyl-2,6-bis(((phenylmethyl)imino)methyl)phenol (HL) have been investigated. It displays high selectivity for Zn2+ and can be used as zinc ion-selective luminescent probe for biological application under physiological conditions. The increase in emission in the presence of Zn2+ is accounted for by the formation of hexanuclear complex [Zn6(L)2(OH)2(CH3COO)8] characterized by X-ray crystallography. An approximately 6-fold Zn2+-selective chelation-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(38 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…Diformyl phenol derivatives have been widely used as uorescence chemosensors on account of their excellent luminescence properties. [64][65][66][67][68] To the best of our knowledge, limited work has been carried out in the development of diformyl phenol based probes for selective colorimetric sensing of Cu 2+ and only two examples are there that represent quenching based detection of Cu 2+ (ESI Chart 1 †). 58,69 Furthermore, involvement of tautomeric equilibrium has not been explored till date.…”
Section: 59-62mentioning
confidence: 99%
“…Diformyl phenol derivatives have been widely used as uorescence chemosensors on account of their excellent luminescence properties. [64][65][66][67][68] To the best of our knowledge, limited work has been carried out in the development of diformyl phenol based probes for selective colorimetric sensing of Cu 2+ and only two examples are there that represent quenching based detection of Cu 2+ (ESI Chart 1 †). 58,69 Furthermore, involvement of tautomeric equilibrium has not been explored till date.…”
Section: 59-62mentioning
confidence: 99%
“…The molar ratio plot indicated that HMB-ASH can bind to Fe(III) at a molar ratio of 2:1. In addition, the apparent binding constant K, calculated by BenesiHildebrand plot (Roy et al 2007), was 3.06 9 10 7 , based on the absorbance changes at 460 nm.…”
Section: Uv Spectra Of Hmb-ash-fe(iii) Complexmentioning
confidence: 99%
“…The saturation point of the fluorescence intensity was regarded as the binding ratio of Al(III) to CPCH. The binding constant between CPCH and Al(III) was calculated using a Benesi-Hildebrand plot, according to previous reports [11,15].…”
Section: Fluorescence Properties Of Cpch-al(iii) Complexmentioning
confidence: 99%